Terror and Internal Migration in Israel. Issue 4 (7th June 2019) - von Borstel, Johanna; Gobien, Tom; Roth, Duncan
Abstract: This paper empirically analyses the effect of terror on internal migration between Israeli subdistricts. Using a unique data-set comprising migration flows for the period 1999–2012 and the number of rocket and non-rocket attacks, we test the hypotheses that terror reduces migration into an affected subdistrict and increases migration out of it. According to our results, the effect of terror on migration is asymmetric as we only find evidence for the first hypothesis. This result remains when we use an instrumental variables strategy that corrects for underreporting of the number of rocket attacks. The largest effects of rocket attacks are found for migration into the Southern subdistrict of Ashqelon as well as into other border regions in Northern Israel, while non-rocket attacks also have substantial effects in the more populous centres of Jerusalem and Tel Aviv.